Pilot study of hemoglobinopathies in newborns of the Rafael Calvo maternity clinic of Cartagena, Colombia (Colombia Medica, 2012)
Introduction: The hemoglobinopathies are a heterogeneous group of congenital anemias from Africa, Asia and the Mediterranean. Due to the migration of this population have spread worldwide, especially in Latin America and the Caribbean region, which Cartagena de Indias is included, with a large proportion of people of African descent. The lack of routine programs that include an appropriate methodology for precise identification of those affected and carriers, it impossible to know the real behavior of this disease in our country and an early and appropriate to the patients before the disease manifests itself and produces its serious consequences.Objective: To estimate the incidence and describe the epidemiological profile of hemoglobinopathies in newborns Rafael Calvo Maternity Clinic of Cartagena, in the period from January to June 2010.Methods: Prospective descriptive study of a population of 1729 newborns. Samples were collected cord blood on filter paper. Isoelectric focusing electrophoresis (IEF )was used to separate the haemoglobins.Results: 94.4% (1633samples) were normal (hemoglobinFA), 4.5% (78samples) were heterozygous for haemoglobin S (HbFAS), 1% (17samples) were heterozygous for haemoglobin C (hemoglobinFAC) and 0.1% (1 sample) was double heterozygous SC (hemoglobinFSC).Conclusion: Due to the high incidence of hemoglobinopathies found in this pilot study highlights the importance and necessity of establishing an obligatory neonatal screening in the city of Cartagena, in order to make a timely diagnosis and monitoring of affected and carrier.